ANALISIS KARAKTERISTIK KEWIRAUSAHAAN, ADOPSI TEKNOLOGI DAN LITERASI KEUANGAN TERHADAP KINERJA UMKM DI KOTA BATAM - Audrey Lismawaty; Erni Yanti Natalia (SCIENTIA JOURNAL, 2025)
This study aims to determine whether entrepreneurial characteristics, technology adoption, and financial literacy have an influence on the performance of MSMEs (Micro, Small, and Medium Enterprises) in Batam City. The population in this study consists of MSME actors registered with the Department of Cooperatives and Micro Enterprises in Batam City. The data collection technique used in this study was a questionnaire distributed to MSME actors in Batam City via the Google Forms platform. The data analysis techniques employed include descriptive analysis, data quality tests, classical assumption tests, multiple linear regression, and hypothesis testing. The results of this study show that entrepreneurial characteristics have a positive and significant effect on the performance of MSMEs in Batam City, as evidenced by a significance value of 0.005 ≤ 0.05. The test results also indicate that technology adoption has a positive and significant effect on MSME performance in Batam City, with a significance value of 0.000 ≤ 0.05. Financial literacy was also found to have a positive and significant influence on MSME performance in Batam City, indicated by a significance value of 0.002 ≤ 0.05. Simultaneous testing using the F-test shows that entrepreneurial characteristics, technology adoption, and financial literacy collectively have a positive and significant effect on the performance of MSMEs in Batam City. This research contributes to the improvement of MSME performance in Batam City.